Pelaksanaan Program Sim Online Dalam Rangka Pelayanan Prima Kepolisian Oleh Anggota Satlantas Polres Cianjur - Syabani, Azizul Widya (Police Studies Review, 2020)
The background of this research is to use the era of technological advancements, using a stack of Driving License applicant queues, and the number of practice brokers. The purpose of this study is to describe the application of Online Driving License, to describe disadvantages in implementing the Online Driving License program, describing the factors that influence the process of making Online Driving License. The author uses research literature and conceptual literature. Based on the theories and concepts used are basic management theories and basic function of management theories by George R. Terry. This research uses qualitative methods, with field research methods. Data collection techniques that can be used are interviews, observation, and study of documents. Presentation of data using data analysis techniques through data reduction, data presentation and conclusions. Describe the mechanism of implementing Online Driving License with the theory of the Basic Function of Management to achieve Excellent Police Services. Describe disadvantages in the implementation of Online Driving License by using the theory of Basic Functions and Basic Management Elements in order to achieve Excellent Police Service, Describe the factors that enhance the Online Driving License program by using the theory of Basic Management Elements in order to achieve Prime Police Services. The use of Online Driving License has been running at the Cianjur Police Station, but in its implementation it still has shortcomings that can hinder the achievement of Excellent Police Services. Spent in order to do another innovation compiling the central server down.